ANALISIS KONSEPTUAL MANAJEMEN MUTU DI MADRASAH DAN PONDOK PESANTREN - Khoiriah Khoiriah; Zulmuqim Zulmuqim (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this study was to conceptually analyze the quality management in Madrasah and Islamic boarding schools. As for the approach, this research is a research library, which means that research is carried out based on written work. The results of this study indicate that to carry out quality management there needs to be a reliable manager/principal. To support the effectiveness and efficiency of their performance, a school/madrasah principal must have several special competencies including professional competence, competency in educational and management insight, personality competence, social competence. The concept of quality management of madrasah and pesantren is related to the optimization of management functions in managing the quality of the pesantren ranging from quality strategic planning, market research, SWOT analysis, key events, strategic plans, developing long-term institutional strategies, quality policies, and quality plans, costs and quality benefits, costs of prevention and failure, up to monitoring and evaluation and quality control.